2022
DOI: 10.1177/20503121221124762
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fatty liver and its correlation with glycemic control in patients with type 2 diabetes mellitus attending Dessie Comprehensive Specialized Hospital, Northeast Ethiopia

Abstract: Objectives: The purpose of conducting this study was to assess fatty liver disease and its correlation with glycemic control in type 2 diabetes mellitus patients. In addition, evaluation of associated factors and correlation analysis between the fatty liver index and hemoglobin A1C level in patients with type 2 diabetes mellitus was another aim of this study. Methods: A hospital-based cross-sectional study was conducted among type 2 diabetes mellitus patients attending at diabetes clinic of Dessie Comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…This review consisted of nine cross-sectional and one case control studies published between 2011 and 2023. The studies were conducted in 6 different Africa countries, with majority coming from Nigeria (n=3) [2426], followed by Ethiopia (n=2) [27, 28], Morocco (n=2) [29, 30], and one each from Egypt [31], Ghana [32], and Sudan [33]. A total of 1667 T2D participants were involved, with the sample size ranging from 80 to 281 across studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This review consisted of nine cross-sectional and one case control studies published between 2011 and 2023. The studies were conducted in 6 different Africa countries, with majority coming from Nigeria (n=3) [2426], followed by Ethiopia (n=2) [27, 28], Morocco (n=2) [29, 30], and one each from Egypt [31], Ghana [32], and Sudan [33]. A total of 1667 T2D participants were involved, with the sample size ranging from 80 to 281 across studies.…”
Section: Resultsmentioning
confidence: 99%
“…The quality score across studies ranged from 8 to 3, with a mean score of 6.1. Majority (n=6) of the studies were of low risk of bias, having a score above 7 [2528, 30, 32]. In contrast, four studies fell below a cut-off score of 5, indicating a higher risk of bias [24, 29, 31, 33].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is no data regarding the population prevalence of NAFLD in Ethiopia, few hospital and institution based studies have tried to assess the prevalence of NAFLD in patients with diabetes. These studies found a higher prevalence of NAFLD ranging between 58.4 and 73% was found [6,7].…”
Section: Introductionmentioning
confidence: 99%